Danger: High Voltage-The Role of Voltage-Gated Calcium Channels in Central Nervous System Pathology - Schampel, Andrea; Kürten, Stefanie (Cells, 2017)
Voltage-gated calcium channels (VGCCs) are widely distributed within the central nervous system (CNS) and presumed to play an important role in the pathophysiology of a broad spectrum of CNS disorders including Alzheimer's and Parkinson's disease as well as multiple sclerosis. Several calcium channel blockers have been in clinical practice for many years so that their toxicity and side effects are well studied. However, these drugs are primarily used for the treatment of cardiovascular diseases and most if not all effects on brain functions are secondary to peripheral effects on blood pressure and circulation. While the use of calcium channel antagonists for the treatment of CNS diseases therefore still heavily depends on the development of novel strategies to specifically target different channels and channel subunits, this review is meant to provide an impulse to further emphasize the importance of future research towards this goal.
EVALuna2:35214